Design procedure of temporary plain con crete slab inside deep excavation - Nilsson, Gustav; Öhman, Rasmus (My University, 2021)
Regard urbanization and exploitation of already densified urban areas, develop ment of areas with disadvantageous construction conditions are made. Regard this, deep excavations are commonly used to manage complex foundations, especially in Gothenburg, where deep excavations are made in soft clay. When performing exca vation in clay, plain concrete slabs are commonly used as struts, but also as working platform to ensure a good working environment. For these concrete slabs there is no specified approach listed in Eurocode, or in no further governing guidelines within the industry. The aim with the thesis is mainly about to evaluate and establish an appropriate design procedure for slabs made of plain concrete used during excavation in soft clay. Literature studies have been made to identify factors that influence the design of plain concrete slabs. The objective was to establish a suitable design procedure that could be used as a general approach, with the intention that the analogy of the design procedure should be inspired by people within the industry, but also on fundamental requirements stated in Eurocode 2. To gather information from the industry, interviews with experts was performed. It was discovered during the interviews that there was no common procedure, or approach when designing these kind of plain concrete slabs, which strengthened our thesis. However, in summary the interviews contributed with important facts and thoughts that have inspired the analogy of the final design procedure. Finally the analytical and FE-analyses was performed, where the analytical design procedure was validated with the FE-software Abaqus CAE. Further a sensitivity analyse was conducted, where the slab was evaluated regarding different forced eccentricities. The result of the analyse confirmed that the design loads are strictly affected by eccentricities regarding initial conditions and heave.
Keywords: Excavation, Clay, Concrete slab, FE-analysis, Plain Concrete, Buckling